PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, BUDAYA ORGANISASI, DAN SISTEM REWARD TERHADAP KINERJA KARYAWAN PADA PT. CITRA GARDEN (CIPUTRA GROUP) - Prasojo, Rosana Tri Setyo; Ekowati, Dian; Agustina, Tri Siwi (PT Naureen Digital Education, 2024)
Low leadership ability in a transformational leadership style, unclear organizational culture, and a poor reward system can improve employee performance. Weakening employee performance will have an impact on achieving company goals and success. The aim of this research is to find out and analyze the influence of transformational leadership style, organizational culture and reward systems on employee performance at PT. Citra Garden. The sample consists of 60 employees. The research method uses a quantitative approach. The data analysis techniques used are data normality test, multicollinearity test, heteroscedasticity test, multiple linear regression, coefficient of determination (R2), simultaneous test (F) and partial test (T). The results of this research show that partially and simultaneously, transformational leadership style, organizational culture and reward systems have a positive and significant effect on employee performance at PT. Citra Garden shows that the better the transformational leadership style, organizational culture and reward system will improve employee performance.